2016
DOI: 10.1016/j.celrep.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Gain-of-Function Screen Identifies the Williams-Beuren Syndrome Gene GTF2IRD1 as a Mammary Tumor Promoter

Abstract: Summary The broad implementation of precision medicine in cancer is impeded by the lack of a complete inventory of the genes involved in tumorigenesis. We screened in vivo ~1,000 genes, that are associated with signaling for positive roles in breast cancer, using lentiviral expression vectors in primary MMTV-ErbB2 mammary tissue. Gain-of-function of five genes, including RET, GTF2IRD1, ADORA1, LARS2, and DPP8 significantly promoted mammary tumor growth. We further studied one tumor promoting gene, the transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Furthermore, high expression of GTF2IRD1 was an independent poor prognostic factor in CRC. Huo et al revealed that high GTF2IRD1 expression correlated with poor overall survival in patients with breast cancer, lung cancer, and ovarian cancer . These clinical findings strongly supported that GTF2IRD1 is a tumor‐promoting oncogene in human cancers, including CRC.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, high expression of GTF2IRD1 was an independent poor prognostic factor in CRC. Huo et al revealed that high GTF2IRD1 expression correlated with poor overall survival in patients with breast cancer, lung cancer, and ovarian cancer . These clinical findings strongly supported that GTF2IRD1 is a tumor‐promoting oncogene in human cancers, including CRC.…”
Section: Discussionmentioning
confidence: 87%
“…We identified 8 genes that satisfied the criteria described above. Among the 8 genes, we focused on GTF2IRD1 (Figure A) because this gene has been reported to promote mammary tumor growth . GTF2IRD1 mRNA expression in tumor tissues was 4.57‐fold higher than that in normal tissues ( P < .0005; Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the particularly complicated processes involved in the occurrence and development of tumors, [ 12 , 13 ] which may be caused by the regulation of cell growth and proliferation. [ 14 ] In addition, abnormal expression of tumor-associated genes may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated the particularly complicated processes involved in the occurrence and development of tumors (17,18). It may be caused by the regulation of cell growth and proliferation (19).…”
Section: Discussionmentioning
confidence: 99%